Recent Biochemical Advances in Antitubercular Drugs: Challenges and Future - Jain, Akanksha; Kumar, Rajesh; Mothsra, Poonam; Sharma, Atul K.; Singh, Anil Kumar; Kumar, Yogesh (Current Topics in Medicinal Chemistry, 2024)
Tuberculosis (TB) is one of the leading causes of death world-wide after AIDS. It infects around one-third of global population and approximately two million people die annually from this disease because it is a very contagious disease spread by Mycobacterium tuberculosis. The increasing number of drug-resistant strains and the failure of conventional treatments against this strain are the challenges of the coming decades. New therapeutic techniques aim to confirm cure without deterioration, to reduce deaths, contagions and the formation of drug-resistant strains. A plethora of new diagnostic tests are available to diagnose the active tuberculosis, screen latent M. tuberculosis infection, and to identify drug-resistant strains of M. tuberculosis. When effective prevention strategies do not prevail, high rates of early case detection and successive cures to control TB emergence would not be possible. In this review, we discussed the structural features of M. tuberculosis, Multi drug resistance tuberculosis (MDR-TB), extremely drug-resistant tuberculosis (XDR-TB), the mechanism of M. tuberculosis infection, the mode of action of first and second-line antitubercular drugs, the mechanism of resistance to the existing drugs, compounds in preclinical and clinical trial and drugs presently available for the treatment of tuberculosis. Moreover, the new diagnostic techniques to detect M. tuberculosis are also discussed in this review.
Keywords: Anti-tuberculosis drugs